Cataloging for Consortial Collections: A Survey. Issue 2 (17th February 2018) - Deng, Shi; Sotelo, Aislinn; Culbertson, Rebecca
ABSTRACT: Libraries face many challenges in making electronic resources accessible and discoverable. In particular, the exponentially incre-asing number of licensed and open access electronic resources and the dynamic nature of consortial collections (platform changes, title transference between packages, and package overlap) present challenges for cataloging and discovery. From March 21 to April 10, 2017, the authors performed a selected review of library literature and conducted a survey of library consortia worldwide to ascertain the cataloging models, strategies, and advanced technological tools used to ensure discovery of consortial collections. The findings from the literature review and survey are summarized in this article.